2011
DOI: 10.1038/onc.2011.284
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of 14-3-3ζ in cancer cells activates PI3K via binding the p85 regulatory subunit

Abstract: The ubiquitously expressed 14-3-3 proteins regulate many pathways involved in transformation. Previously, we found that 14-3-3ζ overexpression increased Akt phosphorylation in human mammary epithelial cells. Here, we investigated the clinical relevance and molecular mechanism of 14-3-3ζ overexpression-mediated Akt phosphorylation and the potential impact on breast cancer progression. We found that 14-3-3ζ overexpression was significantly (P = 0.005) associated with increased Akt phosphorylation in human breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 32 publications
4
77
0
Order By: Relevance
“…25 Thus, 14 --3 --3s is not likely to participate in the activation of pro-survival signaling downstream of the ShcA SH2 domain. We further demonstrate that 14 --3 --3z specifically co-immunoprecipitates with wild-type ShcA, and not the ShcR397K mutant, in mammary tumor lysates, which is consistent with the observation that 14 --3 --3z activates the PI3K/AKT pathway by recruiting the p85 regulatory subunit 19,26 (Figure 4d). However, we cannot exclude the possibility that one or more of the remaining 14 --3 --3 family members are recruited to the SH2 domain of ShcA to enhance breast cancer cell survival.…”
Section: Resultssupporting
confidence: 74%
“…25 Thus, 14 --3 --3s is not likely to participate in the activation of pro-survival signaling downstream of the ShcA SH2 domain. We further demonstrate that 14 --3 --3z specifically co-immunoprecipitates with wild-type ShcA, and not the ShcR397K mutant, in mammary tumor lysates, which is consistent with the observation that 14 --3 --3z activates the PI3K/AKT pathway by recruiting the p85 regulatory subunit 19,26 (Figure 4d). However, we cannot exclude the possibility that one or more of the remaining 14 --3 --3 family members are recruited to the SH2 domain of ShcA to enhance breast cancer cell survival.…”
Section: Resultssupporting
confidence: 74%
“…This is a plausible scenario because proinflammatory cytokines can also affect other biological processes that control Akt function such as protein synthesis 2 and/or Akt targeting/shuttling, 2 which is known to be important for controlling Akt destiny and function. 39 14-3-3ζ stimulates PI3K signaling 59 and also activates PDK1, thus its presence could be important but not essential 60 to induce Akt activation, those properties in 14-3-3ζ could explain in part the tumor-promoting function attributed to 14-3-3ζ upregulation. 61 Additionally, the ratio maintained between the dimeric and monomeric forms of 14-3-3ζ might have a role in controlling Akt activity; and it is possible that oscillations in the amount of p14-3-3ζS58 are necessary not only to maintain the Akt signal but also to control its cellular localization, which is important because Akt phosphorylates at least 100 non-redundant substrates in different cell compartments.…”
Section: Discussionmentioning
confidence: 99%
“…76 Previous study has showed that overexpression of 14-3-3zeta in cancer cells activates PI3K/ AKT signal. 77 FOBISIN101 could be developed as a new inhibitor of 14-3-3zeta, and serve as a novel agent for cancer intervention. Current 14-3-3zeta-targeting approaches are limited to knockdown experiments and peptide inhibitors, but discovering 14-3-3zeta-interacting molecules and developing a specific antibody or inhibitor that recognizes and blocks the functions or activation of 14-3-3zeta may indicate a new field for 14-3-3zeta-targeting therapy in clinical application.…”
Section: Rnaimentioning
confidence: 99%